2017
DOI: 10.18632/oncotarget.23026
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-19a acts as a prognostic marker and promotes prostate cancer progression via inhibiting VPS37A expression

Abstract: Prostate cancer (PCa) is a leading cause of cancer-related deaths among males worldwide. However, the molecular mechanisms underlying the progression of PCa remain unclear. Despite several reported miRNAs in prostate cancer, these reports lacked system-level identification of differentially expressed miRNAs in large sample size. Moreover, it's still largely unknown how miRNAs result in tumorigenesis and progression of PCa. Therefore, by analyzing three public databases, we identified 16 upregulated miRNAs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…miRs regulate ~60% of all human protein coding genes, indicating that miRs serve important roles in physiological and pathological behavior, including cell proliferation, cycle, apoptosis, metastasis, embryogenesis and differentiation (10). The dysregulation of miRs has been recently reported in different types of malignancies, including OS (11), prostate cancer (12), breast cancer (13) and colorectal cancer (14). Abnormally expressed miRs may serve tumor suppressive roles or oncogenic roles in tumorigenesis and tumor development, which depend on the biological functions of their target genes (15).…”
Section: Introductionmentioning
confidence: 99%
“…miRs regulate ~60% of all human protein coding genes, indicating that miRs serve important roles in physiological and pathological behavior, including cell proliferation, cycle, apoptosis, metastasis, embryogenesis and differentiation (10). The dysregulation of miRs has been recently reported in different types of malignancies, including OS (11), prostate cancer (12), breast cancer (13) and colorectal cancer (14). Abnormally expressed miRs may serve tumor suppressive roles or oncogenic roles in tumorigenesis and tumor development, which depend on the biological functions of their target genes (15).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, for lack of specific data in text for RFS, the relevant HRs and its confidence intervals of Fu et al [17] extracted by the Kaplan–Meier Curves with Engauge Digitizer 9.8 as well as the spreadsheet calculator designed by Tierney et al [33] did not support the significance claimed in the original article. The data were collected by two independent authors (Xiangyu Deng and Kaige Ma) from Fu et al [17] for several times using the methods described above whose accuracy had been proved by many researches [47–49]. The extracted data were always consistent but significantly different from the original articles.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-19a is also involved in tumor development by promoting cell proliferation and migration, as well as by reducing apoptosis. For example, Liu et al reported that miR-19a promotes cell proliferation and migration in colorectal cancer cells and accelerates tumor growth in xenograft mice [39]; Fu et al, demonstrated that miR-19a overexpression exerts its oncogenic activity by stimulating cell proliferation, cycle, growth and migration [50]. Finally, Paiva et al, suggested that the development of thyroid cancer derived from miR18a and miR19a altered expression depends primarily on cell-specific proteins [51].…”
Section: Discussionmentioning
confidence: 99%